2013
DOI: 10.3102/0034654313477212
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Reading Interventions for Students With Reading Difficulties After Grade 3

Abstract: This synthesis extends a report of research on extensive interventions in kinder-garten through third grade (Wanzek & Vaughn, 2007) to students in Grades 4 through 12, recognizing that many of the same questions about the effectiveness of reading interventions with younger students are important to address with older students, including (a) how effective are extensive interventions in improving reading outcomes for older students with reading difficulties or disabilities and (b) what features of extensive inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
199
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(225 citation statements)
references
References 40 publications
13
199
1
1
Order By: Relevance
“…Results show that students who were in the Full CSR condition (i.e., received CSR once a week in social studies and once a week in science across a school year) earned significantly higher reading comprehension scores on the GMRT than students in BAU classes without CSR. The modest effect size (g = 0.18) is on par with similar rigorous large scale experimental studies that have found positive effects for reading comprehension instruction on standardized measures when subject to the real-world competing demands of teaching in urban schools (e.g., Fletcher & Wagner, 2014;Vaughn et al, 2011;Wanzek et al, 2013). We found no differences in GMRT scores between students in the BAU group and students in the Partial CSR condition (i.e., received CSR only once a week), the unintended treatment group formed due to scheduling conflicts that disrupted the design of a double dosage of CSR for students.…”
Section: Student Outcomesmentioning
confidence: 76%
“…Results show that students who were in the Full CSR condition (i.e., received CSR once a week in social studies and once a week in science across a school year) earned significantly higher reading comprehension scores on the GMRT than students in BAU classes without CSR. The modest effect size (g = 0.18) is on par with similar rigorous large scale experimental studies that have found positive effects for reading comprehension instruction on standardized measures when subject to the real-world competing demands of teaching in urban schools (e.g., Fletcher & Wagner, 2014;Vaughn et al, 2011;Wanzek et al, 2013). We found no differences in GMRT scores between students in the BAU group and students in the Partial CSR condition (i.e., received CSR only once a week), the unintended treatment group formed due to scheduling conflicts that disrupted the design of a double dosage of CSR for students.…”
Section: Student Outcomesmentioning
confidence: 76%
“…Despite the use of multi-tiered response to intervention approaches, there continues to be a small proportion of "treatment resisters" who fail to respond sufficiently to even the most powerful evidence-based approaches [131,132]. In such circumstances, it is understandable that students, parents, teachers and clinicians will search for alternative approaches.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…This process is in many cases slower than gaining decoding accuracy, which appears to be acquired very fast in transparent orthographies . For children with reading disabilities, problems in fluency have turned out to be very persistent Eklund, Torppa, Aro, Leppänen, & Lyytinen, 2015; and rather difficult to remediate, at least with respect to normative levels of reading Wanzek et al, 2013). Despite these facts, studies on reading fluency interventions have shown that significant increases in reading fluency can be achieved (for reviews, see Chard, Vaughn, & Tyler, 2002;Therrien, 2004;Wolf & Katzir-Cohen, 2001) and that these gains have in some studies promoted reading comprehension (Breznitz, 2006;Therrien, 2004; however, see Gellert, 2014;Scammacca et al, 2007;Soriano, Miranda, Soriano, Nievas, & Felix, 2011).…”
Section: Reading Fluency Intervention In Transparent Orthographiesmentioning
confidence: 99%
“…In conclusion, while naming and reading speed deficits are persistent in their nature, they seem not to be resistant to intervention. Because young children appear to benefit more from reading intervention Wanzek et al, 2013), early identification, careful planning, accurate targeting of the intervention and multifaceted training in which the unique characteristics of the individual child and the orthography are taken into account may prevent the cumulative negative effects of dysfluent reading.…”
mentioning
confidence: 99%